Social distancing during the COVID-19 pandemic: quantifying the practice in Michigan - a "hotspot state" early in the pandemic - using a volunteer-based online survey - Andrea E. Cassidy-Bushrow; Mohammed Baseer; Karen Kippen; Albert M. Levin; Jia Li; Ian Loveless; Laila M. Poisson; Lonni Schultz; Ganesa Wegienka; Yueren Zhou; Christine Cole Johnson (BMC, 2021)
Abstract Background Public Health policies related to social distancing efforts during the COVID-19 pandemic helped slow the infection rate. However, individual-level factors associated with social distancing are largely unknown. We sought to examine social distancing during the COVID-19 pandemic in Michigan, an infection "hotspot" state in the United States early in the pandemic. Methods Two surveys were distributed to Michigan residents via email lists and social media following COVID-19 related state mandates in March; 45,691 adults responded to the first survey and 8512 to the second. Staying home ≥ 3 out of 5 previous days defined having more social distancing. Logistic regression models were used to examine potential factors associated with more social distancing. Results Most respondents were women (86% in Survey 1, 87% in Survey 2). In Survey 1, 63% reported more social distancing, increasing to 78% in Survey 2. Female sex and having someone (or self) sick in the home were consistently associated with higher social distancing, while increasing age was positively associated in Survey 1 but negatively associated in Survey 2. Most respondents felt social distancing policies were important (88% in Survey 1; 91% in Survey 2). Conclusions Michiganders responding to the surveys were both practicing and supportive of social distancing. State-level executive orders positively impacted behaviors early in the COVID-19 pandemic in Michigan. Additional supports are needed to help vulnerable populations practice social distancing, including older individuals.